DETERMINATION OF FERRITE-CEMENTITE INTERLAMELLAR SPACINGS IN STEELS, USING COMPUTER TECHNOLOGY - D. A. Novick (Литьë и металлургия)
The algorithm of determination of an average inter-plate distance according to the computer image of the microstructure, enabling to improve degree of work automation of metallurgist is offered.